Real-time Pricing in Power Markets: Who Gains? - Anette Boom; Sebastian Schwenen (Copenhagen Business School (CBS), Department of Economics, 2013)
We examine welfare e ffects of real-time pricing in electricity markets. Before stochastic energy demand is known, competitive retailers contract with final consumers who exogenously do not have real-time meters. After demand is realized, two electricity generators compete in a uniform price auction to satisfy demand from retailers acting on behalf of subscribed customers and from consumers with real-time meters. Increasing the number of consumers on real-time pricing does not always increase welfare since risk-averse consumers dislike uncertain and high prices arising through market power. In the Bertrand case, welfare is the same with all or no consumers on smart meters.
hdl:10398/8766
Keywords: D42; D43; D44; L11; L12; L13; 330; Electricity; Real-time Pricing; Market Power; Efficiency